Geochemical modeling of water-rock interaction in the ophiolitic aquifers of Northern Calabria - Critelli, Teresa; Pantano, Pietro; Apollaro, Carmine; Marini, Luigi (My University, 2013)
This study was developed in two distinct parts with the ultimate aim to investigate the weathering processes of the metabasalts and serpentinites of Northern Calabria, taking into account the dissolution kinetics of relevant mineral phases. In the first part, a laboratory experimental work has been carried out on two suitably characterized rock samples, a metabasalt and a serpentinite, to determine the whole-rock dissolution rates and, consequently, the kinetic parameters of each constituting mineral in these specific rocks, at 25 °C and different pH values. Mixed-flow reactors were used to perform this experimental work. Incidentally, it must be recalled that: (i) although there are many laboratory studies aimed at the determination of the dissolution rates of separate (single) minerals, less is known about the dissolution rates of individual minerals in multimineralic rocks and (ii) in geochemical modeling, the dissolution rates measured on separate mineral are customarily utilized to estimate the dissolution path of the overall rock, assuming that the dissolution rate of a separate mineral is equal to that of the same mineral in a given rock. However, the experimental results of in this study contradict this hypothesis. Indeed, it turned out that: (i) dissolution rates of individual minerals obtained from the dissolution experiments of whole rocks are significantly different from those of separate minerals and (ii) the dissolution rates of individual minerals exhibit minor differences to each other and appear to be close to the whole-rock rate. This behavior is probably constrained by the sufficiently abundant mineral(s) of lowest dissolution rate, preventing the dissolution of other faster-dissolving mineral grains as long as these do not come in contact with the aqueous phase. The second part of the study has been devoted to simulate the rock-to-water release of elements and their fate in the groundwaters interacting with metabasalts and serpentinites by means of two different reaction-path-modeling approaches. In the first approach, kinetic parameters of relevant minerals were taken from the geochemical literature and the progressive dissolution of metabasalts and serpentinites cropping out in Northern Calabria (Italy) was simulated by means of the EQ3/6 software package, version 8.0, adopting the Double Solid Reactant Method (DSRM). In the second approach, the whole-rock kinetic parameters, retrieved from the dissolution experiments on the metabasalt were used in the modeling exercise. The results of the two reaction-path-modeling approaches are in agreement with analytical data for natural waters but the second approach appears to be more accurate than the first one. The main lesson learned from this study is that the dissolution rates of individual minerals retrieved from the dissolution experiments of whole rocks are significantly different from those of separate minerals. This invalidate the assumption on the equality of these rates which is commonly adopted in geochemical modeling. These findings have important consequences on the understanding of the rock-to-water release of chemical elements and their fate in natural waters.
Scuola di Dottorato "Archimede" in Scienze ,Comunicazione e Tecnologie, Ciclo XXVI Ciclo XXVI, a.a. 2007-2013
Keywords: Geochimica; Acqua; Roccia